Saudi Arabia Charity and the Institutionalization of Indonesian Salafism - Jajang Jahroni (Al-Jami'ah Research Centre, 2020)
[This article primarily discusses the links between Saudi Arabian Islamic charity organizations and the development of Salafism in Indonesia and how these links facilitate the institutionalization of Salafi groups. It specifically deals with the issues of how Islamic charity help Salafi groups create their institutions and how the Salafis distribute these charities to their own members. It also describes how they managed to survive when the flow of Saudi funds was no longer reliable. The primary focus of this article is on the way Islamic charity and Islamic charity organizations respond to existing social and political conditions by engaging in social and political activism. International Islamic charity organizations have shaped the transformation of Islamic movements over the last decades. Indonesian Salafi groups have benefitted from charities in various ways and they have enabled Salafi groups to create their institutions in Indonesia. It is no exaggeration to say that Indonesian Salafi groups have become the major players in the distribution of Saudi Arabian charities in the country. This process is inescapably linked with politics which further shapes the transformation of Salafism in Indonesia.[Pembahasan utama artikel ini adalah menjelaskan keterhubungan antara lembaga amal Arab Saudi dengan perkembangan kelompok Salafi di Indonesia dan bagaimana hubungan ini memfasilitasi penguatan organisasi kelompok tersebut. Lebih khususnya adalah bagaimana lembaga amal Islam tersebut membantu mendirikan yayasan serta membagi dana tersebut kepada anggota-anggotanya. Selain itu juga menjelaskan bagaimana yayasan yang terbentuk itu bertahan ketika tidak lagi menerima sumbangan dari Arab Saudi. Intinya adalah tulisan ini menjelaskan cara kerja filantropi Islam dan organisasi amalnya merespon kondisi sosial dan politik dengan terlibat dalam aktifisme. Organisasi filantropi Islam internasional pada dasarnya telah membawa transformasi gerakan Islam lebih dari satu dekade terakhir. Kelompok Salafi Indonesia dengan berbagai cara telah mengambil keuntungan dari dana amal ini dan untuk menguatkan organisasi mereka di Indonesia. Tidak berlebihan jika disebut bahwa kelompok Salafi merupakan pemain utama dalam distribusi dana amal ini di Indonesia. Proses ini merupakan hal yang tak bisa dihindarkan dari kaitan politik dimana telah banyak berpengaruh pada trasnformasi Salafisme di Indonesia.]